The Development of Islam in The Mughal Time - Nur Fatimah, Friska (Rihlah: Jurnal Sejarah dan Kebudayaan, 2022)
It is thought that commercial networks allowed Islam to spread to India in the seventh century. The history of Islam's entrance in India, where the majority of the population is Hindu, and how it evolved there to give rise to the Indian Muslim community, cannot be isolated from the development of Islam during the Mughal era. Zainuddin Muhammad Babur (1482-1530 AD), who established the Mughal empire, ruled during its height from the time of Akbar (1556-1506 AD). That was the center of Islam's glories in India during the height of the Mughals' power under Sultan Akbar. both in terms of the advancement of civilization, thought, the economy, the government, and science, the arts, and culture. specifically, the height of the last Mughal empire due to a weak leader, the Mughals' decline soon after. The library was used as the primary research source for this investigation. Therefore, all of the data used in this study came from texts that dealt with this issue. Keywords: Development; Islam; Mughals; India